2022
DOI: 10.1007/s00384-022-04190-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: association between obesity/overweight and surgical complications in IBD

Abstract: Purpose While the prevalence of obesity in inflammatory bowel disease (IBD) patients is rapidly increasing, it is unclear whether obesity affects surgical outcomes in this population. This meta-analysis aims to assess the impact of obesity/overweight on patients undergoing surgery for IBD. Methods Databases (PubMed, Web of Science, Cochrane Library, and Springer) were searched through September 2021. The meta-analysis included patients with surgically trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Patrizia Burra 1 Marianna Arvanitakis 2,3 Jorge Amil Dias 4 Michael Bretthauer 5,6 Ana Dugic 7,8 Daniel Hartmann 9 Patrick Michl 10 Thomas Seufferlein 11 Joana Torres 12,13 Hans Törnblom 14 Monique E. van Leerdam 15 Shira Zelber-Sagi 16,17…”
Section: Research and Development Investment To Provide Innovative Pr...mentioning
confidence: 99%
See 3 more Smart Citations
“…Patrizia Burra 1 Marianna Arvanitakis 2,3 Jorge Amil Dias 4 Michael Bretthauer 5,6 Ana Dugic 7,8 Daniel Hartmann 9 Patrick Michl 10 Thomas Seufferlein 11 Joana Torres 12,13 Hans Törnblom 14 Monique E. van Leerdam 15 Shira Zelber-Sagi 16,17…”
Section: Research and Development Investment To Provide Innovative Pr...mentioning
confidence: 99%
“…Obesity and inflammatory bowel disease Twenty percent of paediatric 7 and 40% of adult 8 patients with IBD are overweight or obese A western‐type diet is thought to contribute to obesity and IBD 9 Obesity and/or visceral adiposity may increase the risk for developing surgical complications, hospitalisation and post‐operative recurrence in patients with IBD 10 , 11 , 12 , 13 , 14 …”
Section: Obesity and Chronic Digestive Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has turned out to be an increasing global burden in recent decades and, together with the still rising number of new IBD cases in developing countries, it should be perceived as a risk factor for IBD. The observations from clinical research aiming to determine the actual role of obesity in the premorbid period of IBD are quite ambiguous [ 20 , 21 , 22 , 23 ]. One of the large cohort studies suggested that obesity present in the early stage of adolescence was positively associated with an early diagnosis of CD, before the age of 30, but inversely correlated with a future diagnosis of UC at any age [ 10 ].…”
Section: Introductionmentioning
confidence: 99%